(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
This pedagogical intervention occurred in a federal institute of education science and technology with the participation of students of the 4th year of a technical course in aquaculture integrated to high school. The aim of this research was to analyze the use of active methodologies in the teaching of concepts in Pathology and Parasitology and evaluate the students’ perception about the application of these methods in the professional practice of the aquaculture technician. In the production of data, questionnaires, didactic games and collective discussions/reflections were used. The students demonstrated a positive gain in the production of knowledge and, they realized that the intervention provided moments of reflection about the studied subjects. Through the testimonies and mobilization of knowledge, it was observed that for the students, the active methodologies provided an integrating environment for the learning process. The students were also able to perceive themselves as agents integrated to the teaching proposal, besides correlating the concepts studied with the professional practice.